Opportunities and challenges on composite pressure vessels (CPVs) from advanced filament winding machinery: A short communication - Quanjin, Ma; M. R. M., Rejab; Mohammad, Azeem; Shukur, Abu Hassan; Yang, Binghua; Kumar, A. Praveen (Elsevier Ltd, 2024)
This short communication article critically reviews the modern trends in advanced filament winding machinery and filament wound composite pressure vessels (CPVs) and their potential applications. Firstly, it explores the historical development and advancements in filament winding machinery, which is essential to understand and assess the future state-of-the-art filament winding technique. Secondly, the classification of CPVs is further elucidated concentrating on composition, operating pressure, liner material, and load-bearing capability. It is classified that Type I, II, III, IV, and V of CPVs have been introduced and developed from all-metal to all-composite construction, which significantly reduces the weight of 75% to all-metallic pressure vessels. Thirdly, commercial and potential applications of CPVs have been introduced. Finally, this article provides an outlook on opportunities and challenges of advanced filament winding machinery and CPVs, which gains new insights into integrated design, manufacturing, and performance evaluation on CPVs with artificial intelligence (AI), digitalization, and visualization techniques.